Clinical Strategies to Prevent Acute Respiratory Distress Syndrome - Odeyemi, Yewande E.; Herasevich, Svetlana; Gong, Michelle N.; Gajic, Ognjen O. (Seminars in Respiratory and Critical Care Medicine, 2019)
Acute respiratory distress syndrome (ARDS) remains an important clinical entity in the intensive care unit with a significant impact on morbidity and mortality. Effective therapeutic interventions are limited; thus current research focus has shifted from treatment to the prevention of this pulmonary syndrome. In recent decades, a decrease in the incidence of ARDS has been observed and this reduction is largely due to preventive strategies including safe lung ventilation practices, avoidance of iatrogenic exposures, and improvement in care of predisposing conditions such as sepsis and pneumonia. Early identification of at-risk patients, prompt treatment of predisposing conditions, and adoption of evidence-based best practice including restrictive transfusion strategies, conservative fluid management, avoidance of large tidal volume ventilation, and aspiration precaution practices are key preventive strategies with demonstrated benefits. There are currently no effective pharmacological preventive strategies for ARDS.
Keywords: acute respiratory distress syndrome; acute lung injury; prevention